Role of Information and Communication Technologies in Promoting Financial Inclusion in Rural African Communities in Rwanda - Mugisha, Blessing (International Journal of Technology and Systems, 2024)
Purpose: The aim of the study was to investigate role of information and communication technologies in promoting financial inclusion in rural African Communities Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: This transformation has led to increased savings, facilitated seamless payments, and expanded access to credit, contributing to economic growth, poverty reduction, and enhanced financial resilience in rural communities. Nonetheless, persistent challenges such as limited infrastructure and digital literacy gaps underscore the need for ongoing efforts to fully harness the potential of ICTs, making them a crucial driver of rural development and inclusive growth in Rwanda. Unique Contribution to Theory, Practice and Policy: Diffusion of Innovation Theory, Social Capital Theory & Resource-Based Theory may be used to anchor future studies on role of information and communication technologies in promoting financial inclusion in rural African Communities. Collaborate with technology providers to develop and deploy ICT solutions tailored to the specific needs and preferences of rural African communities. Policymakers should ensure that regulations support innovation, competition, and consumer protection.